Modelling of a Gunn-effect microwave oscillator - Low, Kim Geok. (2009)
Transferred-electron devices utilize the relationship between the electron-drift velocity and the electric field which has been well established by scientists and engineers. In this project, an interactive programme has been developed based on this relationship and a set of well established equations to simulate an oscillator circuit which consists of an oversized n-GaAs Gunn effect diode mounted in an x-band waveguide. The programme, run under Microsoft® Windows 3.1, allows the user to simulate the oscillator's interaction with the waveguide with different diode's specifications. The results of the simulations are analysed so that important parameters like power efficiency, harmonic contents, voltage and current waveforms can be studied with the changes in the diode's specification.